2016
DOI: 10.3390/nu8100613
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene, Lutein and Zeaxanthin May Reduce Faecal Blood, Mucus and Pus but not Abdominal Pain in Individuals with Ulcerative Colitis

Abstract: Background: The main symptom of ulcerative colitis is diarrhoea, which is often accompanied by painful tenesmus and faecal blood and mucus. It sometimes co-occurs with abdominal pain, fever, feeling of fatigue, loss of appetite and weight loss. Some dietary factors have been indicated as important in the treatment of ulcerative colitis. The aim of the study was to analyse the association between retinoid intake (total vitamin A, retinol, β-carotene, α-carotene, β-cryptoxanthin, lycopene, lutein and zeaxanthin)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 52 publications
3
32
0
Order By: Relevance
“…The study included the analysis of diet, as well as the analysis of the disease symptoms in the period of remission. The previous analysis verified the association between dietary intake of carotenoids [16,20], as well as isoflavones [17,21], and the symptoms of ulcerative colitis. However, those studies did not explain fully the influence of diet, so it was hypothesized, that there may be some other diet-related factor which may influence the disease.…”
Section: Study Proceduressupporting
confidence: 56%
“…The study included the analysis of diet, as well as the analysis of the disease symptoms in the period of remission. The previous analysis verified the association between dietary intake of carotenoids [16,20], as well as isoflavones [17,21], and the symptoms of ulcerative colitis. However, those studies did not explain fully the influence of diet, so it was hypothesized, that there may be some other diet-related factor which may influence the disease.…”
Section: Study Proceduressupporting
confidence: 56%
“…Total number of 56 remission ulcerative colitis individuals (19 males and 37 females), age 18-80 years, was recruited for the study. Inclusion criteria were described in the previous publication[ 19 ]. All of the participants provided written consent to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Assessment of the diets was based on the self-reported data from dietary records conducted in three typical random days (2 weekdays and 1 weekend day). The dietary record was conducted on the basis of widely accepted and applied rules, the same as in the case of previously published analysis assessing the retinoid intake in the ulcerative colitis individuals[ 19 ]. To provide the reliable estimates of food intake, participants were instructed about the principles of conducting dietary record, as well as about the necessity of accurate and scrupulous recording of all consumed food products and beverages.…”
Section: Methodsmentioning
confidence: 99%
“…Limited LYC absorption also suggests that the portion remaining in the digestive tract could protect the gastrointestinal system from oxidative damage. Higher intakes of LYC have been associated with a reduced fecal blood, mucus, and pus in subjects with ulcerative colitis in remission . Likewise, animal studies of colitis have demonstrated a reduction in myeloperoxidase, a marker of colon inflammation, after LYC administration both with or without iron.…”
Section: Introductionmentioning
confidence: 99%